2019
DOI: 10.1186/s12939-019-0921-6
|View full text |Cite|
|
Sign up to set email alerts
|

Benefit incidence analysis in public health facilities in India: utilization and benefits at the national and state levels

Abstract: BackgroundBenefit Incidence Analysis (BIA) is used to understand the distribution of health care utilization and spending in comparison to income distribution. The results can illustrate how effectively governments allocate limited resources towards meeting the needs of the poor. In analyzing the distribution of public spending on inpatient, outpatient, and deliveries, this paper represents the most recent BIA completed in India.MethodsIn order to conduct the BIA statistical analysis for this project, 2014 uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(49 citation statements)
references
References 18 publications
4
45
0
Order By: Relevance
“…Their results indicate that for few states the utilization of public healthcare services is pro-poor; however, for many states the distribution is skewed towards the rich. A recent study by Bowser et al, (2019) [31] show that the public outpatient and delivery care is pro-poor in India. The study also documented the state level variations in benefit distribution among the MPCE classes for inpatient and delivery services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicate that for few states the utilization of public healthcare services is pro-poor; however, for many states the distribution is skewed towards the rich. A recent study by Bowser et al, (2019) [31] show that the public outpatient and delivery care is pro-poor in India. The study also documented the state level variations in benefit distribution among the MPCE classes for inpatient and delivery services.…”
Section: Discussionmentioning
confidence: 99%
“…It is also revealed that in most of the states out-patient services is also pro-poor. However, users of public healthcare facilities are forced to spend considerable amount as out-of-pocket to supplement the government services [31]. Another study by Mahal et al, (2001) showed the inequity in subsidy distribution across income groups in India for various healthcare services using BIA [32].…”
Section: Methodsmentioning
confidence: 99%
“…Their results indicate that for few states the utilization of public healthcare services is pro-poor; however, for many states the distribution is skewed towards the rich. A recent study by Bowser et al, (2019) [26] show that the public outpatient and delivery care is pro-poor in India. The study also documented the state level variations in benefit distribution among the MPCE classes for inpatient and delivery services.…”
Section: Discussionmentioning
confidence: 99%
“…The poor population prefers to utilize health services from private providers mainly due to inadequate availability of services from public health facilities, and the problem is so severe in the rural and remote areas in the country. The quality of services delivered by the private providers differs as compared to that in the urban areas (Bowser et al, 2019;Chatterjee et al, 2019). Thus the poor are the victims of unregulated spread of private health services, as they require better care at affordable cost.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%